The Effect of The Flipped Classroom Strategy on Developing Deductive Thinking Among Students of The Department of Art Education In The Subject of Communication Media (Journal of the College of Basic Education, 2025)
The aim of the current research is to identify the effect of the flipped classroom strategy in developing deductive thinking among students of the Art Education Department in the subject of communication media. The researcher adopted a two-group experimental design with a pre-test and a post-test, therefore, to suit it with the sample and objectives of the research. The research sample consisted of students of the Art Education Department, which numbered in number. (43) Male and female students, and through it, the researcher reached the results using the research tool, the achievement test and the deductive thinking test, where the researcher analyzed the data using the statistical package (spss). The results showed, including: The use of the flipped classroom strategy in teaching the subject of communication media is consistent with the requirements of modern education and scientific development. , The adoption.